2007
DOI: 10.1097/ta.0b013e318074d3ac
|View full text |Cite
|
Sign up to set email alerts
|

The Scourge of Methamphetamine: Impact on a Level I Trauma Center

Abstract: METH use in trauma patients increased significantly and was associated with adverse outcomes and a significant financial burden on our trauma center. Evidence-based prevention efforts must be a priority for trauma centers to help stop the scourge of METH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 27 publications
2
42
2
Order By: Relevance
“…Specifically, studies investigating pre-injury amphetamine use have reported inconsistent results. Pre-injury amphetamine use has been significantly associated with increased LOS (13), increased mortality (11), and increased ICU admission (10). However, both the significance and directional trend of these differences varied across studies (10-14).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, studies investigating pre-injury amphetamine use have reported inconsistent results. Pre-injury amphetamine use has been significantly associated with increased LOS (13), increased mortality (11), and increased ICU admission (10). However, both the significance and directional trend of these differences varied across studies (10-14).…”
Section: Discussionmentioning
confidence: 99%
“…At a larger societal level, the financial burden of methamphetamine use on communities is significant. In the U.S., the average cost of healthcare per methamphetamine user was 9% higher than that for non-users, and methamphetamine users were less likely to be insured compared with non-users (Swanson et al, 2007). Beyond direct health care costs, resources forgone because of reduced productivity among methamphetamine users may pose a bigger economic burden on a community.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies are fraught with testing bias in part because those who acknowledge using substances are usually the ones who are tested [17] . In their retrospective chart review of 4,932 patients, Swanson et al [18] managed to minimize such bias by testing all trauma patients who were cooperative or had a urinary catheter for substance use. They demonstrated that MA-positive patients were twice as likely as those testing negative to have a violent mechanism of injury (e.g.…”
Section: Introductionmentioning
confidence: 99%